Hemangiosarcoma of the nasal planum in cats: five cases (2010–2021). Issue 12 (December 2022) - McGrath, Alysha M; Cook, Matthew R; Culp, William TN; Oblak, Michelle L; Oramas, Alberto; Bertran, Judith; Tremolada, Giovanni; Lapsley, Janis; Selmic, Laura E
Case series summary: Nasal planum tumors are rare in cats, with squamous cell carcinoma over-represented. Other skin tumors have been reported in this location and though hemangiosarcoma frequently occurs on the skin of the head, these tumors localized to the nasal planum have not been specifically reported. The objectives of this study were to report the clinical findings and outcomes in cats diagnosed with hemangiosarcoma of the nasal planum. Medical records from four different institutions were reviewed to identify cats with a definitive diagnosis of hemangiosarcoma of the nasal planum. Five cats met the inclusion criteria. One cat was treated with palliative radiation therapy (RT) alone, two cats had lesions removed via an excisional biopsy by the primary care veterinarian and two cats had excisional biopsies performed at a referral institution. All four cats that received surgical treatment were treated with adjuvant strontium-90 therapy. The cat receiving palliative RT alone was lost to follow-up 311 days after treatment. At the time of writing, the survival time for 2/3 cats receiving surgery and strontium-90 was 365 days and 1381 days, respectively. One cat receiving this combination of therapy was lost to follow-up immediately after treatment. One cat developed tumor recurrence and a revision surgery via nasal planectomy and upper lip resection was performed 376 days following the initial surgery. Following revision, palliative RT was pursued. The cat was still alive at the time of writing 618 days after the initial procedure, with no evidence of recurrence. Relevance and novel information: In this case series, surgery was the primary treatment used, but due to the location, only narrow or incomplete surgical margins were possible. RT (strontium-90 and/or palliative) was utilized to decrease the risk of recurrence.